BLT Corp the first pectin production plant in the Philippines : a plant design - Balmes, Ma. Raisah Averiel P.; Lesiguez, Mary Diane E.; Tabada, Dexter R.
The Industrial and Chemical sector of the Philippines Industry are continuously growing over the past few years. A number of innovations and manufacturing plants have been built to produce fresh product sold in the commercial market. BLT Corp. has decided to mass produce pectin. Pectin is a binding and thickening agent usually used for pharmaceutical and food industries. Incidentally, the building of a pectin production plant in the country is a bold move since it would be the first of its kind to be erected in the Philippines. The innovation in our process is the use of new and cheaper raw materials than what is out in the market today. Traditionally, pectin is sourced from fresh mango peels. The whole production process is a combination of mechanical and chemical process, and is divided into three (3) main sections namely: i) Pretreament, ii) Product Conversion and iii) Product Purification. In order to assess the viability of the first pectin production plant, a market is also presented in this paper. It is shown in the market study that the Philippines completely imports the pectin in needs for the pharmaceutical and food industry from outside the country. This means that BLT Corps main competition is the import sales of pectin, particularly from countries in Asia. This will give the company an advantage in adjusting to more competitive prices to the foreign producers that have costly shipping and distribution chargers. There is a wide range of potential customers in the downstream industries especially in pharmaceutical and food manufacturing companies. The local supply of pectin is non-existent, while the foreign supply is costly. A good location for the plant is within the vicinity of the Visayan Region, particularly in Cebu, because of its proximity to the possible customers, the pharmaceutical plants. Also, the bulk of the mango processing plants in the country is found in Cebu. This would minimize the cost for transportation of the raw materials to the processing plant, and from the processing plant to the target customers, The energy consumption of the whole processing plant is low compared to that of other plant since the required temperatures for the involved processes such as drying and extraction are less than 100 celsius, with values of 65 celsius and 80 celsius, respectively. Also, the whole production process requires pressure levels only slightly higher than ambient conditions, hence the minimal need for compressors.